CONCENTRATION OF TRACE METALS IN ROCKY OYSTER (SACCOSTREA GLOMERATA) AND HARD CLAM (MERETRIX LYRATA) IN HAIPHONG COAST - Dung, Le Quang (Vietnam Journal of Marine Science and Technology, 2014)
In order to understand the present status of heavy metal contamination in Haiphong coast, rocky oyster (Saccostrea glomerata) and hard clam (Meretrix lyrata) were examined. The concentration of nine elements (As, Cd, Mn, Cr, Co, Cu, Pb, V and Zn) was determined in whole tissues of these species from Phu Long, Do Son and Quan Muc in March 2012. The result indicated that Zn, Cu, Mn and As were dominant elements, whereas Co, Cr, V, Cd, Pb were minor elements in both species. The metal concentrations in these species were apparently different. While extremely high concentrations of Zn, Cu and Cd were found in the oysters and these were much higher than those in the clams, the clam tended to highly accumulate Mn, V, and Cr and these levels were higher than those in oysters. Comparison of heavy metal concentrations in these species between sites was discussed to determine the poteintial metal contamination in the study areas. The study suggested that these bivalve species are good biomonitors for water quality in Haiphong coast in particular and the North Vietnam coast in general.